Effect of five hours of mixed exercise on urinary nitrogen excretion in healthy moderate-to-well-trained young adults - Clauss, Matthieu; Burkhardt, Meike; Wöber, Sophie; Skålhegg, Bjørn Steen; Jensen, Jørgen (Frontiers in Nutrition, 2024)
Carbohydrates and fats are the primary energy substrates during exercise, but proteins can also contribute. When proteins are degraded in the body, the amino groups are mainly converted to urea and excreted. Therefore, nitrogen excretion has been used as a marker of protein degradation, but a clear conclusion has yet to be reached on the effect of exercise on nitrogen excretion. Thus, we tested whether exercise increases nitrogen excretion. Fifteen young, healthy, moderate-to-well-trained participants (4 females, 11 males, VO2max 54.4 ± 1.7 mL•kg -1 •min -1 ; mean ± SEM) participated in a randomized, balanced cross-over design investigation consisting of one day with 5 hours of exercise (exercise day, EX) and one day with no exercise (control day, CON). The participants recorded their dietary intake the day before from 16:00 and throughout the intervention day. They then repeated these dietary intakes on the second trial day. A standardized lunch was provided on both days. In addition, participants were allowed to consume almost protein-free snacks in EX to ensure the same energy balance during both trial days. Urine was collected throughout the whole testing period, and urinary 3-methylhistidine (3-MH) excretion was measured to examine muscular catabolism. The sweat rate was calculated during the exercise period. The urinary nitrogen and 3-MH excretions did not differ significantly between EX and CON (p=0.764 and p=0.953). The sweat rate was 2.55 ± 0.25 L in EX and 0.14 ± 0.15 L in CON (p<0.001), and by estimating sweat nitrogen excretion, total nitrogen excretion was shown to differ with exercise. Our results showed that five hours of mixed exercise did not significantly impact urinary nitrogen and 3-MH excretions in healthy moderate-to-well-trained young adults.